Lecithin nano-liposomal particle as a CRISPR/Cas9 complex delivery system for treating type 2 diabetes - Cho, Eun Yi; Ryu, Jee Yeon; Lee, Han A.Reum; Hong, Shin Hee; Park, Hye Sun; Hong, Kwan Soo; Park, Sang Gyu; Kim, Hong Pyo; Yoon, Tae Jong (Journal of Nanobiotechnology, 2019)
Background: Protein-based Cas9 in vivo gene editing therapeutics have practical limitations owing to their instability and low efficacy. To overcome these obstacles and improve stability, we designed a nanocarrier primarily consisting of lecithin that can efficiently target liver disease and encapsulate complexes of Cas9 with a single-stranded guide RNA (sgRNA) ribonucleoprotein (Cas9-RNP) through polymer fusion self-assembly. Results: In this study, we optimized an sgRNA sequence specifically for dipeptidyl peptidase-4 gene (DPP-4) to modulate the function of glucagon-like peptide 1. We then injected our nanocarrier Cas9-RNP complexes directly into type 2 diabetes mellitus (T2DM) db/db mice, which disrupted the expression of DPP-4 gene in T2DM mice with remarkable efficacy. The decline in DPP-4 enzyme activity was also accompanied by normalized blood glucose levels, insulin response, and reduced liver and kidney damage. These outcomes were found to be similar to those of sitagliptin, the current chemical DPP-4 inhibition therapy drug which requires recurrent doses. Conclusions: Our results demonstrate that a nano-liposomal carrier system with therapeutic Cas9-RNP has great potential as a platform to improve genomic editing therapies for human liver diseases.
Keywords: Blood glucose level; CRISPR-Cas system; Dipeptidyl peptidase; Glucagon-like peptide-1; Liposomal particles; Nanoliposome; Ribonucleoproteins; Type 2 diabetes mellitus; Animals; Blood Glucose; Cell Line; CRISPR-Cas Systems; Diabetes Mellitus, Type 2; Dipeptidyl Peptidase 4; Drug Delivery Systems; Gene Editing; Gene Targeting; Genetic Therapy; Glucagon-Like Peptide 1; Humans; Lecithins; Liposomes; Mice; Mice, Knockout; RNA, Guide; CRISPR-Cas system; Dipeptidyl peptidase-4 gene; Nanoliposome; Type 2 diabetes mellitus